Quantitative methods for measuring patient preferences: Pilot study for patients with localized prostate cancer - Erfányukova, Anna; Klementová, Tereza; Mašková, Barbora; Donin, Gleb (Lékař a technika, 2024)
This pilot study examines patient preferences in patients with localized prostate cancer using quantitative methods for measuring Discrete Choice Experiment (DCE) and Best-Worst Scaling (BWS) type 3. The study focuses on key attributes that may influence patients' treatment decisions. Patients chose one of two or three hypothetical treatment scenarios based on key attributes: risk of erectile dysfunction; urinary incontinence; other side effects; transport to hospital and return to normal activities. Additionally, patients evaluated both methods in terms of difficulty and satisfaction using a Likert scale. Results show that the most important attribute for patients with localized prostate cancer is the risk of erectile dysfunction (36.0%, 29.8%), followed by the risk of urinary incontinence (24.9%, 23.0%). In both attributes, patients wanted to avoid the worst levels and vice versa. The results of preferred attributes did not differ between methods. Patients found the Discrete Choice Experiment method less difficult and were more satisfied with it. This research suggests that quantitative approaches, such as DCE and BWS, can be valuable tools for better understanding patient preferences and integrating them into personalized treatment decision-making.